2022
DOI: 10.20944/preprints202210.0185.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of methods for collecting mosquitoes (Culicidae: Diptera) in canopy and ground strata in the Brazilian Savanna.

Abstract: The hand-net is the standard method for capturing mosquitoes with sylvatic diurnal activity in disease outbreaks in Brazil. However, occupational risks and biases related to the collectors´ abilities and attractiveness are important limitations. In this study, we compared hand-nets with automatic traps (CDC) associated to CO2 and BG-Lure®, in the Vassununga State Park, a Brazilian Savanna protection area. The collections carried out over 27 days, on the ground and the forest canopy. A total of 1,555 mosquitoes… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
(65 reference statements)
1
0
0
Order By: Relevance
“…We sampled deeper into the forest and at a coarser resolution in the present study, where we generally found a peak in richness and diversity towards the edge, which declined beyond 500 m. Species accumulation curves showed that rarer taxa remained to be sampled, particularly at 500 m, although these are less likely to serve as bridge vectors given their relative scarcity. Similar results from other studies highlight the difficulty of sampling mosquito species to saturation at ground level in forested environments [40,41], especially given biases associated with different sampling methods [16,33,42].…”
Section: Discussionsupporting
confidence: 83%
“…We sampled deeper into the forest and at a coarser resolution in the present study, where we generally found a peak in richness and diversity towards the edge, which declined beyond 500 m. Species accumulation curves showed that rarer taxa remained to be sampled, particularly at 500 m, although these are less likely to serve as bridge vectors given their relative scarcity. Similar results from other studies highlight the difficulty of sampling mosquito species to saturation at ground level in forested environments [40,41], especially given biases associated with different sampling methods [16,33,42].…”
Section: Discussionsupporting
confidence: 83%